TWO NEW NAMES IN THE GENUS GARCINIA L - Y. N. Sbetharam (Research Center for Biology, 1982)
Garcinia solomonensis (A.C. Smith) Kosterm. and G. volkensii (Ltbch.) Kosterm. are not valid. Hence the new names Garcinia crassi-folia Seetharam and G. quadrilocularis Seetharam are proposed.